The Attractors of the Common Differential Operator Are Determined by Hyperbolic and Lacunary Functions - Wolf Bayer (International Journal of Mathematics and Mathematical Sciences)
For analytic functions, we investigate the limit behavior of the sequence of their derivatives by means of Taylor series, the attractors are characterized by 𝜔-limit sets. We describe four different classes of functions, with empty, finite, countable, and uncountable attractors. The paper reveals that Erdelyiés hyperbolic functions of higher order and lacunary functions play an important role for orderly or chaotic behavior. Examples are given for the sake of confirmation.